Implementation Of Human Resources Management With Mixed Employment Status And Implications Of Compensation At PT Jasamarga Jogja Solo - Vira Wina Mauliya; Andriyastuti Suratman (International Journal of Business and Quality Research, 2024)
Organizations always need quality human resources with adequate expertise and skills. Every human resource in the organization has the right to receive rights and obligations in accordance with their position and performance. This internship research is related to the application of human resource management with various employment statuses and compensation implications at PT Jasamarga Jogja Solo. The research internship will start from 13 February 2023 to 13 June 2023 located in Yogyakarta. PT Jasamarga Jogja Solo is a toll road business organization. This research uses a qualitative descriptive approach. Data was collected using observation, interview and triangulation research methods with 3 respondent 2 managers and 1 employee of PT Jasamarga Jogja Solo. The results of this research show that the company has provided appropriate rights and obligations based on government regulations and company regulations to contract employees and assigned employees.